Density of states and current–voltage characteristics in SIsFS junctions. (25th June 2021) - Bakurskiy, S V; Neilo, A A; Klenov, N V; Soloviev, I I; Golubov, A A; Yu Kupriyanov, M
Abstract: We study the density of states (DOS) inside superconducting Josephson SIsFS junctions with complex interlayer consisting of a thin superconducting spacer 's' between insulator I and a ferromagnetic metal F. The consideration is focused on the local DOS in the vicinity of a tunnel barrier, and it permits to estimate the current–voltage characteristics in the resistive state of such junctions. We study the influence of the proximity effect and Zeeman splitting on the properties of the system, and we find significant sub-gap regions with non-vanishing DOS. We also find manifestations of the 0- π transition in the behavior of DOS in a thin s-layer. These properties lead to the appearance of new characteristic features on I–V curves which provide additional information about electronic states inside the junction.